Efektivitas Implementasi Intervensi Keperawatan dengan Inovasi “DEKADEE” dalam Mengontrol Gula Darah pada Pasien Diabetes Lansia di Masyarakat - Safaruddin; Rekawati, Etty; Sahar, Juniati (PT. Pubsains Nur Cendekia, 2024)
Introduction: Diabetes Mellitus (DM) is one of the leading non-communicable diseases (NCDs) in Indonesia, ranking as the sixth leading cause of death. The impact of DM on health has been increasingly detrimental over the years, necessitating serious mitigation efforts. As a response, an innovative nursing intervention known as